The Use of Supercritical Fluid Extraction in Carrier Recovery from a Spent Active Carbon–Zinc Acetate Catalyst - Lidia Dąbek (Adsorption Science & Technology)
The present paper is aimed at showing the usefulness of supercritical fluid extraction in the removal of organic substances and zinc from the surface of a dangerous waste product, i.e. spent catalyst employed in the manufacture of vinyl acetate. The possibility of recovering active carbon (the carrier support for the catalyst concerned) so that it may be used in subsequent processes by combining supercritical fluid extraction with hydrochloric acid leaching has been demonstrated.